MSG384 - Introduction to Geometric Modelling - PPSM, Pusat Pengajian Sains Matematik (2022)
Second Semester Examination 2021/2022 Academic Session July 2022 MSG384 - Introduction to Geometric Modelling Duration : 2 hours